Factors predicting the trend of using iTa'leem among lecturers in International Islamic University Malaysia (IIUM) - Abdul Wahab, Siti Aminah; Tengku Mohd Azzman, Tengku Siti Aisha (Universiti Putra Malaysia (UPM), 2019)
The adoption of Learning Management System (LMS) in Malaysia public higher learning institutions (HLIs) is already almost hundred percent. LMS platforms are held instrumental for online learning because embedded with integrated technologies that enable the flexibility of instruction beyond classroom. However, various studies found that usage behavior among educators towards LMS is still an issue. Many educators are still hesitating to utilize the LMS. Hence, more findings are needed to identify the motivational factors that may contribute to the behavior as well as to monitor the possible changing trends of the usage according to place and time. To respond to the above matter in the context of Malaysia public HLI, a cross-sectional survey was administered in August 2017 involving 165 lecturers from International Islamic University Malaysia (IIUM) in both campuses (Gombak and Kuantan). Respondents from twelve faculties were selected by using proportional stratified sampling method. The Technology Acceptance Model (TAM) (Davis, 1985) is used as the main framework and extended with facilitating conditions (FC) as an external variable. The findings show that the Cronbach Alpha value of each variable is between .80 – .97, some direct and indirect associations between the variables are supported, the differences in the trends of using iTa’LeEM (i.e.: IIUM institutional LMS) across different teaching fields have been identified, and the trend of low utilization is solely predicted by the lecturers’ perceived usefulness of the system. In overall, this study adds insight of how lecturers in Malaysia public HLIs view and act toward LMS.